In vitro screening and characterization of lactic acid bacteria from Lithuanian fermented food with potential probiotic properties - Megur, Ashwinipriyadarshini; Daliri, Eric Banan-Mwine; Balnionytė, Toma; Stankevičiūtė, Jonita; Lastauskienė, Eglė; Burokas, Aurelijus (Frontiers in Microbiology, 2023)
The present work aimed to identify probiotic candidates from Lithuanian homemade fermented food samples. 23 lactic acid bacteria were isolated from different fermented food samples. Among these, only 12 showed resistance to low pH, tolerance to pepsin, bile salts and pancreatin. The 12 strains also exhibited antimicrobial activity against Staphylococcus aureus ATCC 29213, Salmonella Typhimurium ATCC 14028, Streptococcus pyogenes ATCC 12384, Streptococcus pyogenes ATCC 19615 and Klebsiella pneumoniae ATCC 13883. Cell free supernatants of isolate 3A and 55w showed the strongest antioxidant activity of 26.37 g/mL and 26.06 g/mL. Isolate 11w exhibited the strongest auto-aggregation ability of 79.96% as well as the strongest adhesion to HCT116 colon cells (25.671 ± 0.43%). The selected strains were tested for its synbiotic relation in presence of prebiotic. The selected candidates showed high proliferation in presence of 4% as compared to 2% galactooligosaccharides. Among the strains tested for tryptophan production ability, isolate 11w produced the highest L-tryptophan levels of 16.63 ± 2.25 μm, exhibiting psychobiotic ability in presence of prebiotic. The safety of these strains was studied by ascertaining their antibiotic susceptibility, mucin degradation, gelatin hydrolysis and hemolytic activity. In all, isolates 40C and 11w demonstrated the most desirable probiotic potentials and were identified by 16S RNA and later confirmed by whole genome sequencing as Lacticaseibacillus paracasei 11w, and Lactiplantibacillus plantarum 40C: following with the harboring plasmid investigation. Out of all the 23 selected strains only Lacticaseibacillus paracasei 11w showed the potential and desirable probiotic property.